'By fire and sword': early English critiques of Islam and Judaism as 'impostures' or political and 'unfree' religions. (14th March 2020) - Yelle, Robert A.
ABSTRACT: Contemporary critiques of Islam and Judaism as political religions have a genealogical connection with older Protestant arguments that religion ought to remain apolitical. At the end of the seventeenth century in England, drawing on older polemics against Muhammad, the theologian Humphrey Prideaux argued that Islam, like Roman Catholicism, was an 'imposture' because it failed to maintain a distinction between religion and politics. The true Gospel introduced a separation between these domains but was misunderstood by the Jews, who expected the Messiah to restore them to national sovereignty. By recovering the role such arguments played in the development of ideas of religious freedom, Yelle's aim is to show that secularism is not non-religious nor religiously neutral, but a doctrine that has privileged certain interpretations of Christianity in the context of interreligious debates.